EFL Students’ Perception Towards English Movies in Improving Speaking Skill - Maharani, Made Diva (Jurnal Ilmu Multidisiplin Indonesia, 2024)
English is very important to master because nowadays almost all industries are looking for people who have English skills so they can talk to foreigners very fluently. Students, especially students majoring in English, really need to master it. One way that can improve speaking skills is to watch English movies. This study aims to analyze students' perceptions of the use of English films in improving speaking skills at Ganesha University of Education. This study used a qualitative research design with data collection using a questionnaire distributed to 4 classes in semester 4. The results showed that students' perceptions of English films improved their speaking skills. Through English films, they learn new vocabulary and how to pronounce it which they can hear from the characters in the film.